FEASIBILITY OF CARPOOLING SCHEME DEVELOPMENT IN BANDUNG CITY FROM THE PERSPECTIVE OF TRAVELER PREFERENCES - Miming Miharja; Annisa Utami (Fakultas Seni Rupa dan Desain ITB, 2018)
The imbalance between supply and demand in Bandung City transport system has been the cause of the declining of this city transport performance. Supply approach by increasing road network capacity is considered as no longer effective due to limited developable road space. Demand approach seems to be a prospective solution to the problem. Among others, carpooling is considered as a promising scheme to reduce traffic volume by increasing average vehicle occupancy rate. The scheme is developed by attracting some travelers whose trip destination are in one corridor to join the same vehicle. This research figures out the feasibility of the implementation of carpooling scheme from the traveler preferences point of view. Based on Arcamanik Residential Area, Bandung City, the result of the research shows that this scheme is potential to be implemented with the percentage of respondent willingness to change mode in the beginning is 93%. However, after ride matching was introduced, respondents willing to join this scheme decline to 71% on leaving and 79% on the way back home. This research furthermore identifies some constraints in fulfilling traveler preference on carpooling scheme. The constraints are on the point to point pick-up system and walking distance preference that cannot totally be fulfilled.